Best dives [ Anguilla, Antigua & Barbuda - Huber, Joyce; Huber, Jon (Hunter travel, 2009)
Based on the classic, Best Dives of the Caribbean, this guide zeroes in on the best dives of Anguilla, Antigua & Barbuda. It includes the latest and best dive and snorkel sites, each rated for visual excellence and marine life. The author's knowledge of t.